Accountant Stereotypes in Korean Dramas - Luhtitis Enggar Rahmasari; Ika Putri Larasati; Rizky Dharana Meidina (Universitas Negeri Malang, 2024)
Purpose: The objective of this study is to investigate how Korean dramas portray stereotypical images of accountants, which is expected to provide literature that explores popular culture in accounting research.Method: This research used a qualitative approach with the thematic analysis method. Four Korean dramas were selected based on ratings and the role of the accountant profession in the dramas for both main and supporting characters. Findings: The results of the study showed that accountants are described as professional, intelligent, and honest beancounters. Positive and negative stereotypes in Korean dramas as popular culture might influence the career option of becoming accountants. This research has been unable to explain why there has been declining interest in the accountant profession. Future studies could involve examining the effect of accountant stereotypes as portrayed in Korean dramas on their viewers.Originality/Value: The visualization of accountants in Korean dramas is considered a new and interesting topic to be investigated. Some previous studies had involved this topic, and there is still some room for improvement. This study is expected to improve some areas, particularly the methods and findings of related topics.